2017
DOI: 10.1038/s41598-017-15198-8
|View full text |Cite
|
Sign up to set email alerts
|

Sialidase inhibitors attenuate pulmonary fibrosis in a mouse model

Abstract: Fibrosis involves increasing amounts of scar tissue appearing in a tissue, but what drives this is unclear. In fibrotic lesions in human and mouse lungs, we found extensive desialylation of glycoconjugates, and upregulation of sialidases. The fibrosis-associated cytokine TGF-β1 upregulates sialidases in human airway epithelium cells, lung fibroblasts, and immune system cells. Conversely, addition of sialidases to human peripheral blood mononuclear cells induces accumulation of extracellular TGF-β1, forming wha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
151
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(164 citation statements)
references
References 92 publications
12
151
1
Order By: Relevance
“…Recently, researchers have reported encouraging findings. One study showed that sialidase inhibitors could attenuate pulmonary fibrosis in mice, suggesting that sialidase inhibitors may be helpful in the treatment of fibrosis (Karhadkar et al, 2017). Another study indicated that C9-BA-DANA inhibits endogenous and ectopically expressed sialidase activity and established NEU1-mediated bioactivities in human airway epithelia, lung microvascular endothelia, and fibroblasts in vitro and murine lungs in vivo (Hyun et al, 2016).…”
Section: Sialidase Inhibitorsmentioning
confidence: 99%
“…Recently, researchers have reported encouraging findings. One study showed that sialidase inhibitors could attenuate pulmonary fibrosis in mice, suggesting that sialidase inhibitors may be helpful in the treatment of fibrosis (Karhadkar et al, 2017). Another study indicated that C9-BA-DANA inhibits endogenous and ectopically expressed sialidase activity and established NEU1-mediated bioactivities in human airway epithelia, lung microvascular endothelia, and fibroblasts in vitro and murine lungs in vivo (Hyun et al, 2016).…”
Section: Sialidase Inhibitorsmentioning
confidence: 99%
“…Mice administered OP at 10 mg/kg/day have similar plasma levels of oseltamivir carboxylate, the active metabolite of OP, with the same area under the curve (AUC) as humans administered OP at 75 mg/kg twice daily [19]. Moreover, a 10 mg/kg dose in mice was effective in blocking mammalian neuraminidase activity in vivo [20,21]. Therefore, mice received vehicle (water) or 10 mg/kg/day oseltamivir phosphate (OP) (Santa Cruz Biotechnology sc-208135A; Dallas, TX) by gavage daily for four weeks.…”
Section: Oseltamivir Phosphate Treatment Studymentioning
confidence: 99%
“…Several studies demonstrated OP blocks endogenous mammalian NEU activity in vitro and in vivo with concentrations in the μM range depending on the cell type and study (compared to nM range for viral NEUs) [20,[37][38][39][40][41][42][43]. We chose a 10 mg/kg dose based on previous studies in mice demonstrating it was effective in blocking mammalian neuraminidase activity in vivo to decrease GM1 levels in T cells [20] and reduce bleomycin-induced lung fibrosis [21]. Although many of these studies suggest OP inhibits NEU1, the major NEU expressed in the kidney, activity of the other NEUs could be compensating if OP does not effectively inhibit all four mammalian NEUs.…”
Section: Plos Onementioning
confidence: 99%
“…At 24 and 48 hours after ORN06 insult, the control mice and some of the ORN06-treated mice were given intraperitoneal injections of 100 µl PBS, or SAP diluted to a dose of 2.5 mg/kg in 100 µl PBS. At day 3, mice were euthanized by CO 2 inhalation, and bronchoalveolar lavage fluid (BALF) was obtained as previously described (55,57). The experiment was performed in accordance with the recommendations in the Guide for the Care and use of Laboratory Animals of the National Institutes of Health.…”
Section: Mouse Model Of Lung Damage and Cytokine Stormmentioning
confidence: 99%
“…Immunochemistry on BALF cell spots and counts of cells was performed as described previously (57,60,61). Slides were incubated with monoclonal antibodies overnight at…”
Section: Staining Of Bronchoalveolar Lavage Fluid (Balf) Cellsmentioning
confidence: 99%